STIMULASI DAN ADAPTASI PADA KEDAI KOPI: Kajian Dua Kedai Kopi di Yogyakarta - Setyaningfebry, Florentina Untung; Purbadi, Yohanes Djarot (Jurnal Arsitektur Komposisi, 2020)
This study aims to reveal patterns of stimulation and adaptation in coffee shops in Yogyakarta. The concept of stimulation and adaptation is a concept that moves humans to organize themselves in space, so that the use of space is maximized and of high quality. A coffee shop is one of the public facilities that is growing and in demand by young people in the city of Yogyakarta. The interior and exterior design of the coffee shop influences visitors in using the space. Each design element becomes a stimulus that plays a role in the adaptation process of visitors. Thus, the concept of stimulus and adaptation occurring in coffee shops is important to disclose as input for the design of public facilities. The research used qualitative research methods, namely behavioral observation and literature study. The study compared two coffee shops to find patterns of stimulus and adaptation in coffee shops as a youth public facility. The literature review method is used to find standard areas for socializing and learning. The results found that stimulation and adaptation in two coffee shops in Yogyakarta occurred in the interior and exterior spaces. The seating layout is an important stimulus and is supported by other design elements.